Case report: Use of three-dimensional technology in criss-cross heart with double outlet right ventricle - Alifu, Ailixiati; Wang, Haifan; Su, Yuntian; Chen, Renwei (Frontiers in Cardiovascular Medicine, 2023)
Background In this case report, we utilized a three-dimensional printing model to replicate the complex anatomy of a criss-cross heart with double outlet right ventricle—an extremely rare congenital cardiac abnormality. This approach facilitated our understanding of the patient's unique condition and enabled us to plan the surgical procedure with greater precision. Case presentation Our department received a 13-year-old female patient who presented with a pronounced heart murmur and a decrease in exercise capacity. Subsequent two-dimensional imaging revealed the presence of a criss-cross heart with double outlet right ventricle—an intricate and uncommon cardiac malformation that poses challenges for accurate visualization through conventional two-dimensional modalities. To address this challenge, we constructed and printed a three-dimensional model using computed tomography data, which enabled us to visualize and understand the complex intracardiac structures and plan surgical interventions with greater precision. Using this approach, we successfully performed a right ventricular double outlet repair, and the patient made a full recovery following the procedure. Conclusion The criss-cross heart with double outlet right ventricle constitutes a complex and uncommon cardiac anomaly that poses considerable challenges in terms of diagnosis and surgical intervention. Employing three-dimensional modeling and printing represents a promising approach, given its potential to enhance the precision and comprehensiveness of the anatomical evaluation of the heart. As a result, this method holds significant promise in facilitating accurate diagnosis, meticulous surgical planning, and ultimately improving clinical outcomes for patients affected by this condition.